AFFECTIVE VARIABILITY, LONELINESS, AND MOMENTARY SATISFACTION. (11th November 2018) - Goodwin, P; Intrieri, R
Abstract: The current study examines whether affective variability across time impacts individual momentary satisfaction. Attention is also given to whether individual dispositional characteristics mediate the relationship between affective variance and momentary satisfaction. Sixty-nine older adults participated in a study examining daily environment and affective experience. The sample of 69 included 50 women and 19 men with an average age of 71.96 (SD = 6.35). Utilizing Experience Sampling Methodology (ESM; Csikszentmihalyi & Larson, 1987), participants were signaled six times daily for seven consecutive days (or 42 observations per person). Signals were sent approximately every two hours between 8 AM and 8 PM. For each signal, participants completed questions related to the objective situation: time of day, current activity, physical location, and companion. Participants also provided information related to their subjective state at the time of each signal via the Positive Affect and Negative Affect Scales (PANAS; Watson, Clark & Tellegen, 1988). Hierarchical linear modeling was used to examine a model predicting momentary satisfaction where affective variability across the 7-day period was located on level 1 and dispositional loneliness was located on level 2. Regression coefficients relating positive and negative affective variability to momentary satisfaction was statistically significant (b=0.016, p<.004 and b=-.048, p=.012). Regression coefficient relating dispositional loneliness to momentary satisfaction was statistically significant for positive and negative affective variability (b=.014, p<.01 and b=-.058, p<.001, respectively). Discussion will focus on the mechanism through which affective variability impacts general and specific well-being.